Cognitive performance following spontaneous subarachnoid haemorrhage versus other forms of intracranial haemorrhage. (January 2014) - Brand, Christine; Alber, Burkhard; Fladung, Anne-Katharina; Knauer, Katharina; König, Ralph; Oechsner, Annette; Schneider, Inga L.; Tumani, Hayrettin; Widder, Bernhard; Wirtz, Christian Rainer; Woischneck, Dieter; Kapapa, Thomas
Abstract Objective. The exact cause of cognitive deficits following intracranial haemorrhage is unclear. This prospective study examines the abilities after spontaneous subarachnoid haemorrhage (SAH), intracerebral haemorrhage (ICH) and chronic subdural haematoma (SDH) to elucidate the cognitive outcome. Patients and methods. Ninety-nine patients with SAH (N = 60), ICH (N = 25), and SDH (N = 14) were followed up for an average of 6 and 12 months post-haemorrhage. Cognitive tests were used to examine attention, memory, concentration, and executive function. Following were used for analysis: 1. the percentage of patients falling below the 25th percentile per test, 2. the general development from the first to second test point and 3. the incidence of significant changes between the test points. Significance was established as p ≤ 0.05. Results. All three types of haemorrhage resulted in deficits as concerns abstract language (53%–75%). The processing speed was below the normal levels in more than 70% of the patients tested. The cognitive performance of SAH patients was similar to that of patients with SDH and ICH patients after 6 months. The number of patients with outcomes falling below the 25th percentile (to some extent more than 75% in patients post-SAH) is high in all patient groups and mostly decreases over the course. Nevertheless, patients with SAH reveal improvements in many more areas than with ICH and SDH (p ≤ 0.006). Conclusions. The cognitive impairments following SAH, ICH and SDH deficits appear to develop in a similar way regardless of the type of haemorrhage. Cognitive improvement is most pronounced in patients with SAH.